English Ivy (Hedera helix): Identification and Control of Diseases in Commercial Greenhouse Production and in Landscapes - David J. Norman; Gul Shad Ali (EDIS)
English ivy has grown in popularity over the last few years as both an indoor and outdoor ornamental vining plant. While English ivy is very disease resistant, there are a few major diseases that will cause economic loss in production and landscape plantings. This 6-page document will assist residential or commercial property owners in identifying various English ivy diseases. Written by David J. Norman and G. Shad Ali and published by the UF/IFAS Plant Pathology Department, August 2018. http://edis.ifas.ufl.edu/pp339